Heiner Müller regista - Lehmann, Hans Thies (Kritik. Rivista di letteratura e critica culturale, 2024)
Heiner Müller’s work stands out in the landscape of German literature in a singular way, like an erratic boulder. But his activity as a director has also taken on a special, even symbolic significance precisely for that German history to which his interest as a writer is directed. While his value as a writer is rarely questioned even by his opponents, the plays he has produced as a director have not met with unanimous critical or public approval. This essay aims to offer an examination of the positive and negative criticism of the plays of this important heir to the theater of Bertolt Brecht.Even as a director, Müller holds fast to the task he set himself as a writer, which can be described with the formula: theater as historical-political commentary. Like his texts, his directing should be understood as a ceaseless “commentary”: an interpreting, unearthing and bringing to light (“archaeology”), a revealing of hidden contradictions. Commentary historically situates models and predecessors, brings out the political “content” of texts through rewriting and reworking.